2022
DOI: 10.1038/s41598-022-11345-y
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based pharmacotherapy for neuropathic pain related to spinal disorders: results from a patient-based assessment

Abstract: Existing guidelines advocate an updated therapeutic algorithm for chronic neuropathic pain (NeP), but pharmacotherapeutic management should be individualized to pain phenotypes to achieve higher efficacy. This study was aimed to evaluate the efficacy of medications, based on NeP phenotypes, and to propose symptom-based pharmacotherapy. This retrospective study was enrolled 265 outpatients with chronic NeP related to spinal disorders. The patients were classified into three groups: spinal cord-related pain, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A randomized, double-blind, placebo-controlled, phase 3 study found mirogabalin to be a promising treatment for patients with SCI-induced neuropathic pain [71]. Another study suggested that mirogabalin was the most effective treatment for paresthesia/dysesthesia; nevertheless, regarding its treatment efficacy, paresthesia/dysesthesia was the most difficult to relieve pain compared with other types of neurological pain [72].…”
Section: Neuropathic Pain After Spinal Cord Injurymentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled, phase 3 study found mirogabalin to be a promising treatment for patients with SCI-induced neuropathic pain [71]. Another study suggested that mirogabalin was the most effective treatment for paresthesia/dysesthesia; nevertheless, regarding its treatment efficacy, paresthesia/dysesthesia was the most difficult to relieve pain compared with other types of neurological pain [72].…”
Section: Neuropathic Pain After Spinal Cord Injurymentioning
confidence: 99%
“…Using these ROIs, the SUV ratio (SUVR) was calculated as SUV max for cervical spinal cord lesions with increased MRI signal intensity in the sagittal plane/SUV mean for the normal cervical spinal cord at the C7/T1 level [27]. The Neuropathic Pain System Inventory (NPSI) was used at the time of (R)-[ 11 C]PK11195 PET/MRI to assess the degree of NeP [28,29]. Each patient gave written informed consent prior to the study.…”
Section: (R)-[ 11 C]pk11195 Pet Imaging In the Rat Spinal Cord Injury...mentioning
confidence: 99%